2011
DOI: 10.1039/c0mb00080a
|View full text |Cite
|
Sign up to set email alerts
|

Probing aromatic, hydrophobic, and steric effects on the self-assembly of an amyloid-β fragment peptide

Abstract: Aromatic amino acids have been shown to promote self-assembly of amyloid peptides, although the basis for this amyloid-inducing behavior is not understood. We adopted the amyloid-β 16-22 peptide (Aβ(16-22), Ac-KLVFFAE-NH(2)) as a model to study the role of aromatic amino acids in peptide self-assembly. Aβ(16-22) contains two consecutive Phe residues (19 and 20) in which Phe 19 side chains form interstrand contacts in fibrils while Phe 20 side chains interact with the side chain of Va l18. The kinetic and therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
120
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(140 citation statements)
references
References 74 publications
20
120
0
Order By: Relevance
“…However, when both mutations are introduced, they actually reduce the growth kinetics, except at very low concentrations (or large τ diff ). These general trends of fibril growth kinetics are fully consistent with experimental results 49 , even though the negative impacts of the double mutation on growth rate appear overestimated. The reason for the overestimation is not entirely clear, though it is likely due to limitations of the protein force field employed.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…However, when both mutations are introduced, they actually reduce the growth kinetics, except at very low concentrations (or large τ diff ). These general trends of fibril growth kinetics are fully consistent with experimental results 49 , even though the negative impacts of the double mutation on growth rate appear overestimated. The reason for the overestimation is not entirely clear, though it is likely due to limitations of the protein force field employed.…”
Section: Resultssupporting
confidence: 87%
“…Interestingly, the CHA mutations are often non-additive with the double mutation showing a smaller perturbation relative to the WT that one or both of the single mutants. This is a nontrivial prediction that appears consistent with the experimental measurements of fibril growth kinetics 49 . Inspection of Fig.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The self-assembled morphologies of peptide nanostructures formed in these experiments are summarized in Figure 2; a detailed account of the various assembly preparations and the results obtained is given as a Supplementary Results section in the Supporting Information. Briefly, transmission electron microscopy (TEM) showed that Aβ 16−22 alone formed pH-dependent nanostructures as has been reported by others, 40,43,45 i.e., filaments at neutral pH and nanotubes at pH 2.0 ( Figure 2, parts a and e). Interestingly, Aβ 16−22 −F19* displayed similar behavior at neutral pH ( Figure 2b; see also the previous work 31 ) but maintained a filamentous morphology at pH 2.0 ( Figure 2f).…”
Section: ■ Resultsmentioning
confidence: 74%
“…Their stability depends on a variety of interactions including hydrogen bonds, electrostatic interactions, hydrophobic contacts, and aromatic π-π stacking34. Amyloids are linked with many incurable diseases including Alzheimer’s, Parkinson’s, and prion diseases.…”
mentioning
confidence: 99%